2022
DOI: 10.3389/fnut.2022.987921
|View full text |Cite
|
Sign up to set email alerts
|

Low fat diet versus low carbohydrate diet for management of non-alcohol fatty liver disease: A systematic review

Abstract: Although there is a consensus on beneficial effects of a low calorie diet in management of non-alcoholic fatty liver disease, the optimal composition of diet has not yet been elucidated. The aim of this review is to summarize the results of current randomized controlled trials evaluating the effects of low fat diet (LFD) vs. low carbohydrate diet (LCD) on NAFLD. This is a systematic review of all the available data reported in published clinical trials up to February 2022. The methodological quality of eligibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
(90 reference statements)
0
6
0
Order By: Relevance
“…However, no significant improvements in BMI, blood pressure, fasting blood glucose (FBG), or C-reactive protein (CRP) levels were observed. A recent metaanalysis pooling five studies failed to demonstrate differences in H-MRS measurements, weight loss, intrahepatic fat levels, or liver enzyme levels such as AST and ALT [85]. Nonetheless, individual studies showed significant effects of both diets on MASLD compared to a standard diet [86].…”
Section: Low-carb and Low-fat Dietmentioning
confidence: 99%
“…However, no significant improvements in BMI, blood pressure, fasting blood glucose (FBG), or C-reactive protein (CRP) levels were observed. A recent metaanalysis pooling five studies failed to demonstrate differences in H-MRS measurements, weight loss, intrahepatic fat levels, or liver enzyme levels such as AST and ALT [85]. Nonetheless, individual studies showed significant effects of both diets on MASLD compared to a standard diet [86].…”
Section: Low-carb and Low-fat Dietmentioning
confidence: 99%
“…Various nutritional interventions targeting a weight loss ≥ 5% has shown to be effective in the management of MAFLD[ 14 , 23 , 24 ]. Aim of all forms of nutritional interventions for MAFLD is to reduce the proportion of macronutrient content of the diet to achieve total energy deficit by restricting intake of simple carbohydrates, saturated fat, and added sugars, along with adoption of healthier eating options like a Mediterranean diet.…”
Section: Management Approach To Mafldmentioning
confidence: 99%
“…[ 13 , 15 ] A systematic review assessing randomized controlled trials found that low-fat diet appears to be more successful in reducing in transaminase levels in NAFLD. [ 16 ] The recommended dietary intake of fatty acids for adults should be 20% to 35% of daily energy intake. [ 13 ] However, this ratio is approximately 40% of daily energy intake on Western-type diets.…”
Section: Introductionmentioning
confidence: 99%